High‑k Materials with Low Dielectric Loss Based on Two Superposed Gradient Carbon Nanotube/Cyanate Ester Composites - Wang, Binghao; Qin, Dake; Liang, Guozheng; Gu, Aijuan; Liu, Limei; Yuan, Li (Journal of physical chemistry. C, 2013)
Higher dielectric constant, lower dielectric loss, and good processing characteristics have been the goal for developing high-k materials in actual cutting-edge applications. The distribution, motion, and the rearrangement of space charges are the key factors in determining the dielectric properties of a material; however, few reports focus on this subject. Here, materials with high dielectric constant and low dielectric loss, consisting of two superposed gradient multiwall carbon nanotube (MWCNT)/cyanate ester (CE) composites, coded as [g-MWCNT/CE]2, were uniquely prepared. When the loading of MWCNTs is 0.5 wt %, either MWCNT0.5/CE or [g-MWCNT0.5/CE]2 composite shows the largest dielectric constant of its corresponding type of composites, the value is 136 or 306 (at 1 Hz); meanwhile, the dielectric loss tangent at 1 Hz of [g-MWCNT0.5/CE]2 material is 0.21, only about 2.9 × 10–5 times the value of the MWCNT0.5/CE composite. By investigating the distribution of space charges, the unique dielectric behavior of the [g-MWCNT/CE]2 materials is found to result from the reinforced space charge polarization and subdued leakage current induced by the presence of the “conductor fault” between the two superposed gradient composites. These interesting data suggest that the special structure of [g-MWCNT0.5/CE]2 materials is beneficial to fabricate high-k composites with low dielectric loss.